Using infographics in the news bulletins of Arab satellite channels - Alqudaimi, Hamood Radman (Journal of Humanities & Social Sciences, 2022)
The study aimed to find out when infographics were used in the news bulletins of Arab satellite channels. The researcher depended on the descriptive approach to answer the questions of the study, using the content analysis method to analyze the news bulletins of Al- Jazeera, Al- Arabiya and Al- Mayadeen channels from 28/12/2020 to 7/2/2021 AD. The study concluded that there is a noticeable use of infographics in the news bulletins of Arab satellite channels, whereas Al- Arabiya channel achieved the largest percentage in using infographics in its news coverage during the study period, It was followed by Al- Jazeera, then Al- Mayadeen, however, Al- Jazeera and Al- Mayadeen channels gained the largest percentage in using infographics in political and diplomatic news while Al Arabiya channel used infographics more in health news. The news report template came at the forefront of news templates using infographics in news bulletins, while the news came second, the news story came third and finally news comments came, the researcher also recommended conducting more studies related to the infographic and its use in satellite news bulletins and programs.